Analisis Exergoeconomic Pada Kompresor Gas Engine Siklus Miller Berbahan Bakar Pome - Fajri, Ahmad Hasnul; Adriansyah, Adriansyah; Mayana, Hendri Candra; Leni, Desmarita (Jurnal Teknik Mesin, 2024)
Energy efficiency is a crucial challenge in energy resource management. One innovative approach to improving efficiency is through exergy and exergoeconomic analysis. Exergy analysis considers not only the quantity of energy but also its quality, based on the second law of thermodynamics. Meanwhile, exergoeconomic analysis integrates exergy analysis with economic aspects, such as cost calculations. This study uses the Tandun Biogas Power Plant (PLTBg) as a case study to evaluate energy efficiency and operational costs. The analysis begins with the collection of economic data, including investment costs, fixed operation and maintenance (OM) costs, and variable OM costs.The results show that the investment cost is $0.016/kWh, fixed OM costs are $0.030/kWh, and variable OM costs are $0.009/kWh. The cost losses due to exergy destruction before the overhaul of the gas engine were recorded at $127.23/hour, with contributions from each component as follows: combustion chamber ($51.63/hour), compressor ($21.62/hour), and turbocharger ($53.98/hour). After the overhaul, the total cost losses significantly decreased to $3.3752/hour, with detailed losses from the combustion chamber ($1.168/hour), compressor ($2.193/hour), and turbocharger ($0.0142/hour). This study demonstrates that exergy and exergoeconomic analysis can identify significant opportunities to improve energy efficiency and reduce operational costs in biogas-based power plants. This approach serves as a practical guideline for optimizing energy systems in the renewable energy industry sector.